Beyond the speculation - Stanimirović, Dalibor (Central European Public Administration Review, 2025)
Purpose: The increasing digitalization of healthcare systems worldwide has been welcomed as a transformative force, yet its actual effects on healthcare business models remain underexplored. Moving beyond the speculation and overly optimistic expectations, this study examines the real impacts of digitalization on the Slovenian healthcare business model. Methodology: A qualitative research approach was employed, combining a comprehensive literature review with semi-structured online surveys. The study surveyed 20 prominent experts responsible for managing national eHealth solutions in Slovenia. Content analysis was used to capture the perspectives of participating experts and systematically map the real impacts of digitalization on the Slovenian healthcare business model. Findings: Results indicate that digitalization significantly impacts the healthcare business model by improving operational efficiency and care coordination, optimizing data accessibility and management, and enhancing patient engagement. However, due to structural and systemic challenges, the impacts of digitalization on the Slovenian healthcare business model remain relatively limited at this stage and largely depend on the effective alignment of technological advancements with health, business, organizational, and socio-economic factors. Practical implications: The findings emphasize that digitalization in healthcare should not be regarded merely as a technological endeavour, but as a strategic driver of comprehensive healthcare and business transformation. For healthcare managers and policymakers, this means investing not only in digital infrastructure but also in governance, organizational processes, business operations, and social dimensions. By doing so, they can maximize the benefits of digital solutions, reduce inefficien-cies, and create a more sustainable, patient-centred healthcare system. The study may assist leaders to identify bottlenecks and prioritize actions that ensure digitalization can bring measurable improvements in service delivery and public health outcomes. Originality: This research contributes novel insights by providing one of the few empirical analyses of digitalization’s impacts on the Slovenian healthcare business model. Rather than relying on assumptions or normative expectations, it integrates the viewpoints of leading national eHealth experts and contextualizes them within broader structural and systemic framework. The study adds value by bridging the gap between global discourses on digital transformation and the realities of a small national healthcare system, thus offering lessons transferable to other countries facing similar challenges of scale, resources, and institutional inertia.
Keywords: business model; digitalizacija; digitalization; healthcare system; impacts; kvalitativna raziskava; poslovni model; qualitative research; vplivi; zdravstveni sistem